Indonesia’s Defense Diplomacy in Advancing ASEAN Agreement on Disaster Management and Emergency Response (AADMER) as a Regulatory Basis for ASEAN First Responder Formation - Ramsi, Oktaheroe; Perwita, Anak Agung Banyu; Hendarwoto, Yermia (Darul Yasin Al Sys, 2025)
Southeast Asia ranks among the most disaster-prone regions globally, owing to its complex geological features and tropical climate. In response, ASEAN established the ASEAN Agreement on Disaster Management and Emergency Response (AADMER), the region’s first legally binding framework for disaster management. Despite its significance, AADMER's implementation faces structural limitations, including the principle of non-interference, disparities in member state capacities, and bureaucratic delays that hinder rapid mobilization during the critical